Preparation method of protective coating for metal connector of solid oxide battery
By combining an oxide-metal bilayer structure with magnetron sputtering, a dense coating was prepared, which solved the problem of balancing coating quality and efficiency in the prior art and achieved high-temperature stability and long-term performance improvement of solid oxide battery connectors.
Patent Information
- Application Number
- CN202511690753.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-18
- Publication Date
- 2026-02-10
AI Technical Summary
Existing coating preparation processes cannot simultaneously achieve high quality, long-term stability, and high efficiency, resulting in performance degradation of solid oxide battery metal interconnects under high-temperature conditions, which fails to meet industrialization requirements.
By employing an oxide-metal dual-layer structure design and a controllable magnetron sputtering process, a dense inner layer of transition metal oxide is first deposited on the surface of the metal connector, followed by the deposition of an outer layer of transition metal alloy, and then a protective coating is formed through annealing.
This method enables the efficient preparation of dense and structurally complete coatings, significantly suppresses element interdiffusion, improves the electrochemical performance and long-term stability of the coatings, reduces contact resistance, and enhances the operational reliability and lifespan of solid oxide batteries.
Smart Images

Figure CN121496341A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of surface engineering technology, and more specifically relates to a method for preparing a protective coating for a metal interconnect in a solid oxide battery. Background Technology
[0002] Solid oxide battery (SOC) technology, as the core of next-generation high-efficiency energy conversion systems, faces significant commercialization challenges due to the performance degradation of its key component, the "metal interconnect," under long-term service conditions. To overcome industry-recognized bottlenecks such as cathode poisoning caused by element volatilization and a surge in contact resistance, constructing a high-performance spinel protective coating on the interconnect surface is considered one of the most feasible technical approaches. However, current coating preparation processes all suffer from inherent limitations in balancing coating quality, process efficiency, and long-term stability, becoming a critical bottleneck restricting the industrialization of SOC technology.
[0003] Specifically, while existing wet processes such as electrophoretic deposition and sol-gel are simple to operate, their film-forming mechanisms result in coatings with loose structures and weak interfacial adhesion, making them prone to cracking and peeling under thermal shock conditions and unable to meet the long-term density requirements under harsh high-temperature conditions. Spraying processes such as atmospheric plasma spraying, while improving deposition efficiency, inevitably introduce interlayer porosity and phase structure instability, significantly weakening the coating's barrier properties and conductive continuity. Existing magnetron sputtering technology also fails to fundamentally resolve this contradiction: if metal mode sputtering is used, the intense interdiffusion of elements during subsequent thermal oxidation will induce a high-resistivity reaction layer and Kirkendall pores, severely degrading electrical properties; if reactive sputtering is used, its deposition rate is too low, leading to high production costs and making it difficult to meet the needs of large-scale manufacturing. This technical bottleneck of "high quality cannot be efficient, and efficient quality cannot be high quality" profoundly reflects the limitations of existing coating preparation methods at the principle level.
[0004] Therefore, there is an urgent need in this field for an innovative coating solution that can break through the above-mentioned technical paradigms. It must be able to simultaneously achieve high densification of the coating, precise control of the spinel phase structure, and effective suppression of the interdiffusion of harmful elements within a short deposition time that is feasible for industrialization, thereby providing a comprehensive solution for SOC connectors that combines excellent protective performance with good process economy. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing a protective coating for a metal interconnect in a solid oxide battery. By combining an oxide-metal bilayer structure design with a controllable magnetron sputtering process, the invention effectively improves the technical problems in the prior art, such as the difficulty in balancing deposition efficiency and coating quality, element interdiffusion, and coating stability.
[0006] To achieve the above objectives, the present invention provides the following solution: One of the technical solutions of this invention is: a method for preparing a protective coating for a metal interconnect in a solid oxide battery, comprising the following steps: Using a transition metal alloy as the target material, a dense inner layer of transition metal oxide is deposited on the surface of a metal interconnect substrate by reactive magnetron sputtering in an oxygen-containing atmosphere. Subsequently, an outer layer of transition metal alloy is deposited on the inner layer of transition metal oxide by metal-mode magnetron sputtering in an inert atmosphere. After annealing, the protective coating is formed.
[0007] Furthermore, the transition metal alloy includes at least two of Mn, Co, Fe, Ni, Cu, Zn, Cr, V, Ti, and Sc.
[0008] Optionally, when the transition metal alloy contains two elements, the atomic percentage range of the two transition metal elements is 1:0.2-5. The specific ratio needs to be determined by comprehensively considering the electronic conductivity and thermal expansion coefficient of the final oxide coating. For example, when the elements in the transition metal alloy are Mn and Co, the atomic percentage can be 1:1-3, preferably 1:2.
[0009] Furthermore, the oxygen-containing atmosphere is provided by a mixture of argon and oxygen gas at a pressure of 0.7-1.2 Pa.
[0010] The volume fraction of oxygen must be greater than the proportion required for sputtering into reactive magnetron sputtering mode. Optionally, the volume fraction of oxygen in the mixed gas is 3-30%.
[0011] Furthermore, the reactive magnetron sputtering is powered by a pulsed DC power supply or an RF power supply, with a sputtering power of 3.5-5.0 W / cm². 2 .
[0012] Furthermore, during the reactive magnetron sputtering, the rotational speed of the metal interconnect substrate is 10-30 rpm, and the temperature is 200-500 ℃.
[0013] Furthermore, the thickness of the transition metal oxide inner layer is 0.2-1.0 μm.
[0014] Furthermore, the inert atmosphere is provided by argon gas at a pressure of 0.7-1.2 Pa.
[0015] Furthermore, the power supply for the metal-mode magnetron sputtering is a DC power supply, with a sputtering power of 3.5-5.0 W / cm². 2 .
[0016] Furthermore, the thickness of the outer layer of the transition metal alloy is 1.0-4.0 μm.
[0017] Furthermore, during the metal-mode magnetron sputtering, the rotational speed of the metal substrate is 10-30 rpm, and the temperature is 200-500 ℃.
[0018] Furthermore, the annealing process has a heating rate of 1-5 °C / min, a temperature of 700-900 °C, and a holding time of 0.5-5 h.
[0019] Optionally, the annealing treatment is performed at a temperature of 800 °C for 2 hours.
[0020] The substrate used for sputtering deposition is a highly conductive metallic material, preferably ferritic stainless steel with a Cr content greater than 16 wt.%.
[0021] The second technical solution of the present invention provides a protective coating for a metal connector of a solid oxide battery, wherein the protective coating for the metal connector of a solid oxide battery is prepared by the above preparation method.
[0022] The third technical solution of the present invention provides an application of the above-mentioned protective coating for solid oxide battery metal connectors in improving the performance stability of metal connectors under high temperature conditions.
[0023] The fourth technical solution of the present invention provides a solid oxide battery connector, wherein the surface of the solid oxide battery connector is provided with the above-mentioned protective coating for a solid oxide battery metal connector.
[0024] The present invention discloses the following technical effects: This invention employs a composite process design of "first reactive sputtering to form a dense oxide inner layer, then metal sputtering to deposit an alloy outer layer," which retains the advantages of reactive sputtering in preparing high-quality coatings while leveraging the high deposition rate of metal sputtering. This continuous process is completed without changing the target material or disrupting the vacuum, and the overall deposition efficiency is significantly improved compared to pure reactive sputtering, effectively solving the efficiency bottleneck problem in the preparation of high-quality coatings.
[0025] This invention effectively suppresses element interdiffusion and optimizes the microstructure of the coating when preparing a protective coating for metal interconnects in solid oxide batteries. Specifically, the pre-deposited dense transition metal oxide inner layer can act as a highly efficient diffusion barrier layer under high-temperature conditions, significantly inhibiting the migration of elements such as Cr and Fe from the substrate to the outside, while delaying the internal diffusion of oxygen ions. This structure can reduce the diffusion depth of Cr by more than 45%, thereby effectively controlling the formation of high-resistance reaction layers and thermally grown oxide layers, ensuring low contact resistance and long-term stability of the interconnect. By pre-introducing atomic oxygen into the inner layer, the element diffusion path and kinetics during the oxidation process of the outer alloy are optimized, effectively avoiding the generation of Kirkendall pores and cracks caused by the mismatch between the diffusion rates of cations and anions, ultimately obtaining a high-quality spinel coating with a complete structure, fine grains, and low porosity.
[0026] The protective coating for metal interconnects in solid oxide batteries provided by this invention has excellent electrochemical performance. Specifically, the coating exhibits low areal resistivity (ASR) and excellent long-term stability. After 1000 hours of oxidation testing at 750 °C, the areal resistivity of the interconnect coated with this coating is significantly better than that of the uncoated substrate and the traditional single-layer coating, providing a reliable guarantee for the long-term stable operation of solid oxide battery stacks.
[0027] The present invention has excellent practicality and economy in the process of preparing protective coatings for metal interconnects of solid oxide batteries. Specifically, the entire preparation process is completed continuously in the same equipment. The process is simple, has good repeatability, does not come into contact with the atmospheric environment, avoids the inefficiency and pollution risks caused by multiple clamping and vacuuming, and improves production efficiency. Attached Figure Description
[0028] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is a schematic diagram of the protective coating preparation process in Embodiment 1 of the present invention.
[0029] Figure 2 The image shows a cross-section of the protective coating in Example 1, where (a) is before annealing and (b) is after annealing.
[0030] Figure 3 The image shows a cross-section of the protective coating in Comparative Example 1, where (a) is before annealing and (b) is after annealing.
[0031] Figure 4The images shown are SEM images, EDS spectra, and line scan results of the protective coating in Example 1, where (a) is the SEM image, (b)-(f) are the EDS spectra, and (g) is the line scan result.
[0032] Figure 5 The following are the SEM images, EDS spectra, and line scan results of the protective coating in Comparative Example 1, where (a) is the SEM image, (b)-(f) are the EDS spectra, and (g) is the line scan result.
[0033] Figure 6 The XRD patterns are of the protective coatings of Example 1 (MCO-MnCo) and Comparative Example 1 (MnCo).
[0034] Figure 7 The weight gain curves of the samples obtained in Example 1 and Comparative Example 1 after oxidation in static air at 650°C for 1000 hours are shown.
[0035] Figure 8 The images shown are SEM images, EDS spectra, and line scan results of the sample obtained in Example 1 after oxidation at 750℃ for 1000 hours. Among them, (a) is the SEM image, (b)-(f) are the EDS spectra, and (g) is the line scan result.
[0036] Figure 9 The images shown are SEM images, EDS spectra, and line scan results of the sample obtained in Comparative Example 1 after oxidation at 750℃ for 1000 hours. Among them, (a) is the SEM image, (b)-(f) are the EDS spectra, and (g) is the line scan result. Detailed Implementation
[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0038] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0039] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0040] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0041] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0042] Unless otherwise specified, all raw materials and reagents involved in the specific embodiments of this invention are commercially available products.
[0043] Unless otherwise specified, room temperature and normal temperature in the specific embodiments of this invention refer to 20-30℃.
[0044] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.
[0045] The metal connector substrates used in the specific embodiments of this invention have all undergone surface pretreatment processes such as rust removal and degreasing, specifically: The surface of the metal connector substrate is polished step by step using metallographic sandpaper ranging from 600# to 2000#. Then, it is placed in acetone, anhydrous ethanol and deionized water in sequence, and ultrasonically cleaned for 15 minutes in each case to thoroughly remove surface oil and particulate contaminants. Finally, it is dried with high-purity nitrogen.
[0046] In some specific embodiments, the present invention provides a method for preparing a protective coating for a metal interconnect in a solid oxide battery, comprising the following steps: S1. Mount the metal connector substrate onto the base of the sputtering vacuum chamber, mount the transition metal alloy target onto the target holder, close the vacuum chamber, and evacuate the vacuum chamber to a vacuum level of 10. -3 Pa or above; The transition metal alloy includes at least two of the following: Mn, Co, Fe, Ni, Cu, Zn, Cr, V, Ti, and Sc. When there are two elements in the transition metal alloy, the atomic percentage of the two transition metal elements is 1:0.2-5, which is determined by comprehensively considering the electronic conductivity and thermal expansion coefficient of the final oxide coating. S2. Introduce a mixture of high-purity argon (99.999% purity) and high-purity oxygen (99.999% purity) into the vacuum chamber, with the oxygen volume fraction being 3-30%. Stabilize the initial working pressure of the vacuum chamber at 0.7-1.2 Pa. Raise the temperature of the metal connector substrate to 200-500 °C and maintain it stable. Perform sputtering using a pulsed DC power supply or an RF power supply at a power density of 3.5-5.0 W / cm². 2 Reactive magnetron sputtering, in which the rotational speed of the metal interconnect substrate is 10-30 rpm, forms a dense transition metal oxide inner layer with a thickness of 0.2-1.0 μm on the surface of the metal interconnect substrate. S3. Cut off the oxygen supply to the vacuum chamber. Without changing the target material, maintain a stable working pressure of 0.7-1.2 Pa in the inert atmosphere within the same vacuum chamber. Use the same transition metal alloy target material and sputter with a DC power supply at a power density of 3.5-5.0 W / cm³. 2 Metal mode magnetron sputtering was used, with the substrate temperature of the metal interconnect being 200-500 ℃ and kept stable, and the rotation speed being 10-30 rpm. Under these conditions, a transition metal alloy outer layer with a thickness of 1.0-4.0 μm was deposited on the dense transition metal oxide inner layer, forming a transition metal oxide / transition metal alloy composite coating. S4. The metal interconnect substrate with the transition metal oxide / transition metal alloy composite coating is taken out of the vacuum chamber and placed in a muffle furnace. Under static air atmosphere, the temperature is increased from room temperature to 700-900℃ at a heating rate of 1-5℃ / min. After reaching the target temperature, it is held for 0.5-5 hours to allow the outer alloy to fully oxidize, the inner and outer layers to diffuse and fuse with each other, and the spinel phase to crystallize. Then, the temperature is controlled to drop back to room temperature at a rate of 1-5℃ / min to form a single spinel protective coating with uniform composition and dense structure, which is the protective coating used for the metal interconnect of solid oxide batteries.
[0047] The atomic percentage range of the two transition metal elements mentioned in step S1 is 1:0.2-5, which is determined by comprehensively considering the electronic conductivity and thermal expansion coefficient of the final oxide coating. Specifically, within this range, the atomic ratio with the highest thermal expansion coefficient and electronic conductivity is selected.
[0048] The transition metal alloys defined in this invention include two or more elements selected from Mn, Co, Fe, Ni, Cu, Zn, Cr, V, Ti, and Sc. During high-temperature oxidizing annealing, these elements can generate spinel oxides, which, as a protective coating for the linker, effectively reduce the diffusion and oxidation rate of oxygen into the linker's metal matrix, while simultaneously preventing electrode Cr poisoning caused by Cr volatilization in the linker. For example, among the generated spinel oxides, the manganese-cobalt spinel (Mn,Co)3O4 formed from Mn and Co elements exhibits high electronic conductivity and a thermal expansion coefficient close to that of the metal linker.
[0049] The following explanation uses transition metals Mn and Co as examples. However, although this explanation only involves two elements, Mn and Co, it should not be considered a special limitation on the technical solution.
[0050] This invention first employs reactive sputtering to deposit a dense Mn-Co-O oxide (MCO) inner layer on a metal substrate, followed by metal sputtering to deposit an MnCo alloy outer layer, forming an MCO / MnCo composite coating. After annealing, a monolithic (Mn,Co)3O4 spinel protective layer is formed. The core of this invention lies in utilizing the reactive sputtering-prepared MCO inner layer as a diffusion barrier layer, effectively suppressing the diffusion of elements such as Cr from the substrate to the coating, and the diffusion of oxygen into the substrate, during high-temperature annealing and long-term service. This significantly reduces the thickness of the reactive layer and the thermally grown oxide layer, while the main body of the coating is still sputtered using metal sputtering, retaining the advantages of high efficiency and short sputtering time. This composite coating has a dense structure, stable composition, and a good match with the substrate's coefficient of thermal expansion. It also possesses excellent oxidation resistance and low surface resistivity, effectively improving the long-term operational stability and service life of the SOC interconnect.
[0051] Figure 1 This is a schematic diagram of the protective coating preparation process in Embodiment 1 of the present invention.
[0052] Example 1 The preparation steps for the protective coating used in the metal interconnect of solid oxide batteries include: S1. Install the metal connector substrate (commercial-grade 442 ferritic stainless steel) onto the base of the sputtering vacuum chamber. Install the MnCo alloy target (Mn:Co ratio 1:2) onto the target holder. Close the vacuum chamber and evacuate it to a vacuum level of 10. -3 Pa or above; S2. A mixture of high-purity argon (99.999% purity) and high-purity oxygen (99.999% purity) is introduced into the vacuum chamber, with the oxygen volume fraction precisely controlled at 3.2%. The initial working pressure of the vacuum chamber is stabilized at approximately 0.8 Pa. The temperature of the metal connector substrate is raised to 300 °C and maintained stable. Sputtering is performed using a pulsed DC power supply at a power density of 4.39 W / cm². 2 The reactive magnetron sputtering was performed with a metal interconnect substrate rotating at 20 rpm. Under these conditions, a dense MCO oxide inner layer with a thickness of 0.8 μm was formed on the surface of the metal interconnect substrate. S3. Cut off the oxygen supply to the vacuum chamber, without changing the target material, maintain a stable working pressure of 0.7 Pa in the inert atmosphere within the same vacuum chamber, use the same MnCo alloy target, and sputter with a power density of 4.39 W / cm² using a DC power supply. 2 Metal mode magnetron sputtering was used, with the metal interconnect substrate temperature set at 300 °C and kept stable, and the rotation speed at 20 rpm. Under these conditions, a 1.6 μm thick MnCo alloy outer layer was deposited on the dense MCO oxide inner layer, forming an MCO / MnCo composite coating. S4. The metal interconnect substrate with the MCO / MnCo composite coating is removed from the vacuum chamber and placed in a muffle furnace. Under static air atmosphere, the temperature is increased from room temperature to 800 ℃ at a heating rate of 3 ℃ / min. After reaching the target temperature, it is held for 2 h to allow the outer alloy to fully oxidize, the inner and outer layers to diffuse and fuse with each other, and the spinel phase to crystallize. Then, the temperature is controlled to be cooled to room temperature at a rate of 3 ℃ / min to form a uniform and dense single manganese cobalt spinel protective coating (MnCo2O4 spinel protective coating), which is the protective coating used for the metal interconnect of solid oxide batteries.
[0053] Comparative Example 1 The preparation steps of the protective coating include: S1. Install the metal connector substrate (commercial-grade 442 ferritic stainless steel) onto the base of the sputtering vacuum chamber. Install the MnCo alloy target (Mn:Co ratio 1:2) onto the target holder. Close the vacuum chamber and evacuate it to a vacuum level of 10. -3 Pa or above; S2. High-purity argon gas (99.999% purity) is introduced into the vacuum chamber. In an inert atmosphere, the working pressure is stabilized at 0.7 ppm. Sputtering power density is 4.39 W / cm³ using a DC power supply. 2 Metal mode magnetron sputtering was used to deposit a 2.0 μm thick MnCo alloy layer on the metal interconnect substrate at a temperature of 300 °C and kept stable, and a rotation speed of 20 rpm. S3. Take the metal connector substrate with the MnCo alloy layer out of the vacuum chamber and put it into a muffle furnace. Under static air atmosphere, heat it from room temperature to 800 ℃ at a heating rate of 3 ℃ / min. After reaching the target temperature, hold it at that temperature for 2 h. Then, control the cooling rate to room temperature at 3 ℃ / min to form a protective coating.
[0054] Test case The cross-sectional morphology of the coating was observed using scanning electron microscopy (SEM), and the results are as follows: Figures 2-3 As shown.
[0055] Figure 2 The image shows a cross-section of the protective coating in Example 1, where (a) is before annealing and (b) is after annealing. It can be seen that the deposited composite coating exhibits a dense structure. After annealing, the MCO inner layer and the MnCo outer layer have fused into a uniform and dense single-layer manganese cobalt spinel.
[0056] Figure 3 The image shows a cross-section of the protective coating in Comparative Example 1, where (a) is before annealing and (b) is after annealing. It can be seen that the deposited monolayer MnCo coating exhibits a dense structure, and after annealing, pores are generated inside the monolayer coating due to the Kirkendall effect.
[0057] The EDS and line scan results of the interfaces after annealing in Example 1 and Comparative Example 1 are as follows: Figure 4 and Figure 5 As shown.
[0058] Figure 4 The figures show the SEM image, EDS spectrum, and line scan results of the protective coating in Example 1, where (a) is the SEM image, (b)-(f) are the EDS spectra, and (g) is the line scan result. As can be seen from the figures, the thickness of the thermally grown layer (TGO) on the substrate surface is 0.3 μm, while the thickness of the reaction layer (RL) formed by element diffusion between the surface manganese cobalt spinel layer and the TGO layer is also 0.3 μm.
[0059] Figure 5 The figures show the SEM images, EDS spectra, and line scan results of the protective coating in Comparative Example 1. (a) is the SEM image, (b)-(f) are the EDS spectra, and (g) is the line scan result. As can be seen from the figures, the thickness of the thermally grown layer (TGO) on the substrate surface is 0.6 μm, while the thickness of the reactive layer (RL) is 0.5 μm. Compared to the comparative example, the TGO layer thickness in this example is reduced by 50%, and the RL layer thickness is reduced by 40%. Figure 6The figures show the XRD patterns of the protective coatings in Example 1 (MCO-MnCo) and Comparative Example 1 (MnCo). As can be seen from the figures, both coatings formed a single MnCo2O4 spinel structure after annealing.
[0060] The samples obtained in Example 1 and Comparative Example 1 were oxidized in static air at 650°C for 1000 hours, and their weight gain curves were recorded. The results are as follows: Figure 7 As shown, bare steel (commercial grade 442 ferritic stainless steel) is used as a comparison.
[0061] Figure 7 The graph shows the weight gain curves of the samples obtained in Example 1 and Comparative Example 1 after oxidation in static air at 650°C for 1000 hours. The figure shows that after 300 hours of testing, the weight gain per unit area of Example 1 was significantly lower than that of Comparative Example 1 and the uncoated bare steel, demonstrating its better oxidation resistance.
[0062] After oxidizing the samples obtained in Example 1 and Comparative Example 1 at 750℃ for 1000 hours, SEM characterization, EDS characterization, and line scanning were performed. The results are as follows. Figures 8-9 As shown.
[0063] Figure 8 The images show the SEM image, EDS spectrum, and line scan results of the sample obtained in Example 1 after oxidation at 750℃ for 1000 hours. (a) is the SEM image, (b)-(f) are the EDS spectra, and (g) is the line scan result. As can be seen from the figures, the thickness of the TGO layer on the substrate surface of Example 1 is 0.4 μm, and the thickness of the RL layer is 0.9 μm.
[0064] Figure 9 The figures show the SEM images, EDS spectra, and line scan results of the sample obtained in Comparative Example 1 after oxidation at 750℃ for 1000 hours. (a) is the SEM image, (b)-(f) are the EDS spectra, and (g) is the line scan result. As can be seen from the figures, the thickness of the TGO layer on the substrate surface of Comparative Example 1 is 0.8 μm, and the thickness of the RL layer is 0.5 μm.
[0065] comprehensive Figures 8-9 As can be seen, compared with Comparative Example 1, the TGO layer thickness of Example 1 is reduced by 50%. Since the conductivity of the TGO layer is significantly lower than that of other layers, the sample using Example 1 can significantly reduce the impedance during long-term operation and improve the working performance of the fuel cell stack.
[0066] Electrochemical performance testing: The coated connector sample was subjected to an areal resistivity (ASR) test using the DC four-probe method in static air at 750 °C. The test results are as follows: The composite coating sample of Example 1 had an ASR value of 28 mΩ·cm after 1000 hours of oxidation.2 This is significantly lower than the 38 mΩ·cm measured on the single-layer coated sample of Comparative Example 1. 2 .
[0067] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0068] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a protective coating for a metal interconnect in a solid oxide battery, characterized in that the steps include... include: Using a transition metal alloy as the target material, a dense inner layer of transition metal oxide is deposited on the surface of a metal interconnect substrate by reactive magnetron sputtering in an oxygen-containing atmosphere. Subsequently, an outer layer of transition metal alloy is deposited on the inner layer of transition metal oxide by metal-mode magnetron sputtering in an inert atmosphere. After annealing, the protective coating is formed.
2. The preparation method according to claim 1, characterized in that, The transition metal alloy includes at least two of the following: Mn, Co, Fe, Ni, Cu, Zn, Cr, V, Ti, and Sc.
3. The preparation method according to claim 1, characterized in that, The oxygen-containing atmosphere is provided by a mixture of argon and oxygen gas at a pressure of 0.7-1.2 Pa. And / or, the reactive magnetron sputtering is powered by a pulsed DC power supply or an RF power supply, with a sputtering power of 3.5-5.0 W / cm². 2 ; And / or, during the reactive magnetron sputtering, the rotational speed of the metal interconnect substrate is 10-30 rpm and the temperature is 200-500 ℃.
4. The preparation method according to claim 1, characterized in that, The thickness of the transition metal oxide inner layer is 0.2-1.0 μm.
5. The preparation method according to claim 1, characterized in that, The inert atmosphere is provided by argon gas at a pressure of 0.7-1.2 Pa; And / or, the power supply for the metal-mode magnetron sputtering is a DC power supply with a sputtering power of 3.5-5.0 W / cm². 2 ; And / or, during the metal mode magnetron sputtering, the rotational speed of the metal interconnect substrate is 10-30 rpm and the temperature is 200-500℃.
6. The preparation method according to claim 1, characterized in that, The thickness of the outer layer of the transition metal alloy is 1.0-4.0 μm.
7. The preparation method according to claim 1, characterized in that, The annealing process involves a heating rate of 1-5 °C / min, a temperature of 700-900 °C, and a holding time of 0.5-5 h.
8. A protective coating for a metal interconnect in a solid oxide battery, characterized in that, The protective coating for the metal interconnect of the solid oxide battery is prepared by the preparation method according to any one of claims 1-7.
9. The application of the protective coating for a solid oxide battery metal connector as described in claim 8 in improving the performance stability of the metal connector under high-temperature conditions.
10. A solid oxide battery connector, characterized in that, The surface of the solid oxide battery connector is provided with the protective coating for the metal connector of the solid oxide battery as described in claim 8.
Citation Information
Cited By
Protective coating for sofc metallic interconnect surface and its preparation and application
CN122327146A